Why Lhasa de Sela Matters - Goodman, Fred (University of Texas Press, 2019)

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.